THE ROLE OF ARTIFICIAL INTELLEGENCE IN THE EDUCATIONAL PROCESS (Eureka Journal of Education & Learning Technologies, 2026)
Artificial intelligence (AI) is rapidly entering the educational system and becoming a dependable assistant for both students and teachers. It contributes significantly to the improvement of education standards and changing teaching methods. AI offers personalized learning materials for each student, creating the opportunity to take into account their level of understanding and individual needs. Applying AI correctly can lead to achieving quality education and preparing new generations for the challenges of the modern world. Artificial intelligence opens up new possibilities for enhancing the effectiveness of teaching, fostering students' passions, and tailoring each to their own requirements. When artificial intelligence is used properly, it can result in high-quality education and prepare the next generation for the difficulties of the modern world. Artificial intelligence (AI) is quickly entering the educational system and developing into a dependable tool for instructors and students alike. It makes a substantial contribution to raising educational standards and altering instructional strategies. Each learner receives individualized learning materials from artificial intelligence (AI), which makes it possible to consider their unique demands and comprehension ability. The impact of artificial intelligence (AI) on education is examined in this article, along with its advantages, disadvantages, and possibilities for the future. Additionally, instances of AI's successful use in education elsewhere are provided. Furthermore, the paper that follows offers suggestions about the potential of artificial intelligence and its potential future applications in this subject.
Keywords: Artificial intelligence (AI), educational system, learning materials, comprehension ability, ChatGPT, Duolingo, PrepAI, Smartest learning, MATHiaU.